Towards A Global Labour Market In A Knowledge-Dominated Economy - Papoutsakis, Haris (Journal of Knowledge Management Practice, 2010)
In the past thirty years a huge shift has been noticed in the structure of employment. The booming manufacturing sector, traditional employer until the seventies, slowly and gradually gave place to what many researchers call ‘knowledge intensive services’. In a knowledge economy environment, highly skilled workers and skilled or unskilled migrants around the globe compete with each other for the same jobs. Narrow, economic definitions of the labour market fail to elucidate this shift. Broader definitions, including dimensions like professional occupations, skilled labour and immigration, or import of labour force, are provided in order to describe this new, global labour market. After elaborating on this matter, the paper focuses on answering two questions. First, which is the best way to face skills shortages in a knowledge economy? This is important because a skill gaps is a symptom that appears even within a global labour market. It can be quantitative, when there is an excess demand for workers with a particular set of skills; it may also be qualitative, when the skill requirements differ from the skills possessed by the existing labour force. Skill gaps can be transformed into labour shortages and skill shortages can lead to unfilled vacancies. Training offered by employers and changes in education and the migration policies are some of the possible answers examined in the paper. The second question has two branches. To what extent is the above noted shift in employment driven by small businesses? Is the noted transformation towards a knowledge based economy accompanied by a shift to innovative and technology-based start ups or are big corporations still considered most effective for generating and exploiting new forms of knowledge? Answers here vary, especially between Europe and the US, but the research review presented sheds enough light on the issue. Finally, upon concluding, the paper summarises the most important lessons learned through our study, for those who have to navigate in the rough seas of a global labour market in times of a knowledge-dominated economy.